2013
DOI: 10.1080/10942912.2012.654702
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soaking and Germination on Polyphenol Content and Polyphenol Oxidase Activity of Mung Bean (Phaseolus AureusL.) Cultivars Differing in Seed Color

Abstract: 18Five mung bean cultivars varying in seed coat color were analysed for polyphenol content. The 19 effect of soaking and germination on the polyphenol content and polyphenol oxidase activity was 20 investigated. The level of total polyphenols was found to be in the range of 310-340 mg/100 g in 21 whole seeds. Soaking reduced the total polyphenols whereas, germination for 48 hrs increased 22 total polyphenol content by 41-76%. The HTs, CTs and HTs/CTs index increased with increase 23 Downloaded by [University L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…It is a good source of protein, carbohydrate and minerals. Its protein quality is similar to other legumes, such as pigeon pea, chickpea and black gram . Mung bean grains also exhibit a high level of antioxidant activity due to the presence of phenolic compounds.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…It is a good source of protein, carbohydrate and minerals. Its protein quality is similar to other legumes, such as pigeon pea, chickpea and black gram . Mung bean grains also exhibit a high level of antioxidant activity due to the presence of phenolic compounds.…”
Section: Introductionmentioning
confidence: 92%
“…Its protein quality is similar to other legumes, such as pigeon pea, chickpea and black gram. 2 Mung bean grains also exhibit a high level of antioxidant activity due to the presence of phenolic compounds. Major phenolic compounds reported in mung bean are catechin, caffeic acid, ferulic acid, chlorogenic acid, p-coumaric acid, vitexin, isovitexin, quercetin and kaempferol.…”
Section: Introductionmentioning
confidence: 99%
“…Tannin levels may be reduced as a result of lactic acid fermentation, leading to increased absorption of iron, except in some high tannin cereals, where little or no improvement in iron availability has been reported (Ray and Didier 2014). Reduction in polyphenols may be because of the presence of phenolic oxidase during germination (Tian et al 2019;Tajoddin et al 2014). In most of the cereals, Lactobacillus spp.…”
Section: Fermentationmentioning
confidence: 99%
“…Germination of edible seeds typically involves de novo synthesis of bioactive compounds in which many are considered health-enhancing ingredients [1]. Many edible seeds, such as lentils ( Lens culinaris L.), kidney bean ( Phaseolus vulgaris L.), mung bean ( Phaseolus aureus L.), faba bean ( Vicia faba L.), lupin ( Lupinus angustifolius L.), and soybean ( Glycine max ), have been germinated to obtain sprouts with improved nutritional and medicinal values [2,3,4,5]. It has been demonstrated that germination can significantly accumulate diverse bioactive compounds such as polyphenols, gamma-aminobutyric acid, and vitamins, and enhance antioxidant capability in germinated seeds [1].…”
Section: Introductionmentioning
confidence: 99%